PENGARUH MEDIA SOSIAL TIK TOK TERHADAP KECERDASAN KINESTETIK ANAK USIA DINI - Aida Ayu Fitriana; Elisa Novie Azizah; Octavian Dwi Tanto (JCE (Journal of Childhood Education), 2021)
The purpose of this study was to determine the effect of the use of tik tok social media on the kinesthetic intelligence of Group B aged 5-6 years at TK Nusantara Sumberbening, Bringin District, Ngawi Regency. This study used a pre-experimental research design with the type of One-Group Pre-test Post-test Design because there were no parallel classes in the school. The subjects of this study were children of group B TK Nusantara Sumberbening, Bringin District, Ngawi Regency, with a total of 21 students. The data collection method used was participant observation. The data analysis technique used parametric statistics with t test or t-test for small, interrelated samples. Based on the data analysis, it was found that there was an increase in the average score of children's kinesthetic intelligence before and after being given treatment, namely from 52.6 to 67.05. Furthermore, from the results of the calcultion of the t-test formula for a small sample that is interconnected in this study, it shows that tcount> ttable (5.2> 1.7), with a significance level of 5%. This means that the alternative hypothesis (Ha) is acceptable, so the use of social media tik tok is an effective way (has a significant effect) on the Kinesthetic Intelligence of the 5-6 Year Age Group at TK Nusantara Sumberbening, Bringin District, Ngawi Regency.